Edible dragonflies and damselflies (order Odonata) as human food – A comprehensive review - Siddiqui, S.A.; Asante, K.; Ngah, N.; Saraswati, Y.R.; Wu, Yuan Seng *; Lahan, M.; Aidoo, O.F.; Fernando, I.; Povetkin, S.N.; Castro-Munoz, R. (Brill Academic Publishers, 2024)
The rapid growth of the human population leads to a big concern about the food y and demand worldwide. However, due to the reduction in global arable land area, humans need to find alternative food sources to fulfil their needs. Consequently, edible insects have been identified as a promising solution to ameliorate food security and increase global nutrition. Among more than 2,100 identified edible insect species, dragonflies and damselflies (order Odonata) are considered as one of nutritious food resources. Nevertheless, detailed information on the frequency and distribution of consumption of odonatans around the world is scattered and poorly documented. Based on this review, at least 61 out of 1,964 species of odonatans were reported consumed by people worldwide. The most consumed dragonflies (suborder Epiprocta; infraorder Anisoptera) are from the family of Libellulidae, followed by Aeshnidae and Gomphidae, whereas the most consumed edible damselflies (suborder Zygoptera) are from the Coenagrionidae family. Many nutrients, including proteins, lipids, energy, fibre, vitamins, and minerals are abundant in edible odonatans. Moreover, studies reported that humans employed these insects as therapeutic agents to remedy various ailments. Challenges associated with the consumption of edible odonatans include safety concerns, legal frameworks, and limited information on their bioecology which become barrier for their successful mass-rearing. However, because entomophagy is gradually gaining recognition, new and more improved methods of rearing are now being developed including for edible odonatans, encouraging sustainable insect farming. As the world strives to achieve the sustainable development goals, insect farming will pave a way for resources to be utilised for sustainable economic development.